Prevalence and Factors Associated with Sharing of Human Immunodeficiency Seropositivity Status among Serodiscordant Couples in the City of Parakou (Benin) - AGUEMON, BADIROU DIN OWOLADÉ OTONIKOU; Damien Barikissou, Georgia (My University, 2024)
Introduction : In serodiscordant couples, sharing serostatus is a crucial step in the HIV risk management process. The aim of this study was to determine the prevalence and factors associated with serostatus sharing among HIV serodiscordant couples in the city of Parakou. Setting and methods : This study was carried out in the city of Parakou, capital of northern Benin. It was a descriptive, analytical cross-sectional study with non-probability sampling for convenience. Socio-demographic data, as well as data on antecedents, behaviours, social and marital life, were collected using a questionnaire gave to the participants. Clinical and therapeutic data were collected from patients’ medical records and follow-up charts. Data were analyzed and processed using R 4.3.1 software. The significance level was set at 5%, and logistic regression was used to identify potential predictors of shared serostatus among serodiscordant couples in the city of Parakou in 2022. Results : A total of 299 participants in long-term serodiscordant relationships were included in our study. The average age of the subjects was 37.55 ± 10.25 years. Women were the infected partner in 80.27% of cases. The most common level of education was secondary (33.45%). Most respondents (230 subjects, 76.92%) were married. The average duration of the couple’s relationship was 121.68 months ± 96.32. The most frequent screeningcircumstances were : Prevention of mother-to-child transmission (PMTCT) (50.84%) and hospital screening (26.09%). The infected partner shared his or her serostatus with his or her spouse in 47.83% of cases. Potential predictors of serostatus sharing within the couple were: marital status (p < 0.000); household type (p = 0.016); spouse’s level of education (p = 0.004); type of site (p = 0.001) and extended family involvement in conflict management (0.001). Conclusion : The sharing of serostatus within serodiscordant couples needs to be managed in a way that takes into account the social and marital characteristics of the couple.
Keywords: Serodiscordance; Sharing of Serostatus; HIV; Partner; Benin